The Effects of Corporate Identity and Product Knowledge on Consumer Purchase Decision - Asep Saepudin; Edi Ganda Permana; Wursan Wursan; Tine Badriatin (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2022)
The background of this research is that consumer purchasing decisions for the mobile phone Oppo brand are still fluctuating. This is due to Corporate identity, knowledge of the product. Thus, this research focuses on the influence of corporate identity and product knowledge on consumer purchasing decisions. The method used is descriptive qualitative with the following research results. Respondents' responses to corporate identity tend to be good, as well as consumer purchasing decisions. The results of the analysis show that there is a significant influence of corporate identity on consumer purchasing decisions. This means that if corporate identity increases, it will be followed by an increase in consumer purchasing decisions. Respondents' responses to product knowledge tend to be good, as well as consumer purchasing decisions. The results of the analysis show that there is a significant effect of product knowledge on consumer purchasing decisions. This means that if knowledge about the product increases, it will be followed by an increase in consumer purchasing decisions. Respondents' responses to corporate identity and product knowledge tend to be good, as well as consumer purchasing decisions. The results of the analysis show that there is a significant influence of corporate identity and product knowledge on consumer purchasing decisions. This means that if knowledge about the product increases, it will be followed by an increase in consumer purchasing decisions.